Hypervirulent Klebsiella pneumoniae as Unexpected Cause of Fatal Outbreak in Captive Marmosets, Brazil - Guerra, Juliana Mariotti (Emerg Infect Dis, 2020)
After the sudden death of captive marmosets in São Paulo, Brazil, we conducted a histologic and microbiologic study. We found hyperacute septicemia caused by hypermucoviscous sequence type 86 K2 Klebsiella pneumoniae. We implemented prophylactic antimicrobial therapy, selected dedicated staff for marmoset interactions, and sanitized the animals’ fruit to successfully control this outbreak.